Penggunaan Teknologi dalam Manajemen Enterprise Resource Planning (ERP), Sistem Manajemen Informasi serta Otomatisasi Perspektif Islam - Purwanti Purwanti (Lembaga Yasin AlSys, 2025)
Digital transformation has revolutionized modern management paradigms by positioning efficiency and accuracy as core pillars in enhancing organizational competitiveness. This study aims to analyze the integration of technology into managerial practices through the implementation of Enterprise Resource Planning (ERP), Management Information Systems (MIS), and business process automation. A descriptive-analytical approach was employed, combining literature review with empirical observation of digital system implementations in both business and education sectors. The findings indicate that the integration of ERP and MIS enables accurate, transparent, and real-time information flows, directly supporting data-driven decision-making. Furthermore, business process automation accelerates the execution of operational tasks while significantly reducing the risk of human error. These results affirm that the effectiveness of digital management is not solely determined by technological proficiency but also by integrative strategies that align data, systems, and human resource competencies. Consequently, the success of organizational transformation hinges on adaptive capabilities to synergize technology and management as a unified, functional system oriented toward operational excellence and responsiveness to dynamic business environments.